2009
DOI: 10.1111/j.1471-4159.2009.06113.x
|View full text |Cite
|
Sign up to set email alerts
|

Occludin oligomeric assemblies at tight junctions of the blood–brain barrier are altered by hypoxia and reoxygenation stress

Abstract: Hypoxic (low oxygen) and reperfusion (post-hypoxic reoxygenation) phases of stroke promote an increase in microvascular permeability at tight junctions (TJs) of the blood–brain barrier (BBB) that may lead to cerebral edema. To investigate the effect of hypoxia (Hx) and reoxygenation on oligomeric assemblies of the transmembrane TJ protein occludin, rats were subjected to either normoxia (Nx, 21% O2, 60 min), Hx (6% O2, 60 min), or hypoxia/reoxygenation (H/R, 6% O2, 60 min followed by 21% O2, 10 min). After tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
89
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 71 publications
9
89
1
Order By: Relevance
“…Our data showing that tempol prevents the increase in BBB permeability to 14 Csucrose after HR treatment suggest that oxidative stress may also affect the molecular structure of the TJs. Previous work by our laboratory has indicated that the TJ protein occludin is affected by HR (McCaffrey et al, 2009), and its ability to oligomerize is redox sensitive (Walter et al, 2009). These observations led us to investigate the effects of oxidative stress on occludin at both the cellular and molecular level using confocal microscopy and density gradient subcellular fractionation followed by western blot analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our data showing that tempol prevents the increase in BBB permeability to 14 Csucrose after HR treatment suggest that oxidative stress may also affect the molecular structure of the TJs. Previous work by our laboratory has indicated that the TJ protein occludin is affected by HR (McCaffrey et al, 2009), and its ability to oligomerize is redox sensitive (Walter et al, 2009). These observations led us to investigate the effects of oxidative stress on occludin at both the cellular and molecular level using confocal microscopy and density gradient subcellular fractionation followed by western blot analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Occludin oligomers are held together covalently by disulfide bonds (McCaffrey et al, 2009;Walter et al, 2009). These bonds can be disrupted by pathologic conditions such as HR and inflammatory pain, leading to structural changes of the oligomers (McCaffrey et al, 2008;McCaffrey et al, 2009). Changes in the structure of occludin oligomers could potentially influence the ability of the TJ complexes to limit paracellular diffusion of molecules from the blood into the brain.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During inflammation, enhanced oxidative stress can drastically alter the GSH/GSSG ratio toward glutathione GSSG, which prevents oligomeric assembly of occludin. Along this line, inflammation or hypoxia/reoxygenation-induced oxidative stress resulted in reduced occludin oligomerization (279,281). Mice and rat deficient in SOD1 also have decreased expression of occludin, claudin-5, and ZO-1 correlating with excessive ROS generation (260,261,472).…”
Section: Regulation Of Endothelial Junctional Proteins and Associamentioning
confidence: 99%